Edukacja kobiet w kontekście imperialnej polityki narodowej (na przykładzie ziem byłego Wielkiego Księstwa Litewskiego w latach 1830–1860) - Mastianica-Stankiewicz, Olga (Biuletyn Historii Wychowania, 2023)
The article traces the process of elaboration of education policies in women’s education in the Northwest of the Russian Empire by different agents of the imperial state on the central and local levels in the 1830s–1860s. The principal goal is not the history of education in a gendered perspective but rather the history of female social roles and national differences in this troubling imperial borderland. The ethnic and confessional markers of difference in the analysis aimed at producing a complex and dynamic picture of conjuncture of social, national, and gender discourses as well as idiosyncratic local considerations in contradictory efforts of imperial social engineering are complicated by the gender marker.